Lemongrass Extract Possesses Potent Anticancer Activity Against Human Colon Cancers, Inhibits Tumorigenesis, Enhances Efficacy of FOLFOX, and Reduces Its Adverse Effects. (December 2019) - Ruvinov, Ivan; Nguyen, Christopher; Scaria, Benjamin; Vegh, Caleb; Zaitoon, Ola; Baskaran, Kiruthika; Mehaidli, Ali; Nunes, Malika; Pandey, Siyaram
Current chemotherapeutics for metastatic colorectal cancers have limited success and are extremely toxic due to nonselective targeting. Some natural extracts have been traditionally taken and have shown anticancer activity. These extracts have multiple phytochemicals that can target different pathways selectively in cancer cells. We have shown previously that lemongrass ( Cymbopogon citratus ) extract is effective at inducing cell death in human lymphomas. However, the efficacy of lemongrass extract on human colorectal cancer has not been investigated. Furthermore, its interactions with current chemotherapies for colon cancer is unknown. In this article, we report the anticancer effects of ethanolic lemongrass extract in colorectal cancer models, and importantly, its interactions with FOLFOX and Taxol. Lemongrass extract induced apoptosis in colon cancer cells in a time and dose-dependent manner without harming healthy cells in vitro. Oral administration of lemongrass extract was well tolerated and effective at inhibiting colon cancer xenograft growth in mice. It enhanced the anticancer efficacy of FOLFOX and, interestingly, inhibited FOLFOX-related weight loss in animals given the combination treatment. Furthermore, feeding lemongrass extract to APC min/+ transgenic mice led to the reduction of intestinal tumors, indicating its preventative potential. Therefore, this natural extract has potential to be developed as a supplemental treatment for colorectal cancer.